Putting it into practice : developing student critical thinking skills in teacher education--the models, methods, experience and results - Jones, Paula; Haydon, Debbie (Emerald Publishing Limited : Information age publishing, inc., 2012)
Most teachers would agree that they teach reasoning skills in their classes. However, are they explicitly incorporating strategies that teach students to think critically? If so, how do they know these methods are effective? The purpose of this book is to summarize and share a variety of methods for developing students' critical thinking skills. Each chapter focuses on a select teacher education class where the instructor implemented components of the Paul and Elder Model of Critical Thinking.Written from the instructor's point of view, each chapter details how each instructor utilized components of the Paul and Elder Model to support students in the development of their critical thinking skills. Importantly, each instructor's use of the model varied and those variations are shared in detail. Chapter authors found that utilizing components of the Paul and Elder Model resulted in more consistent use of critical thinking skills by students within their teacher education classes. In this practice-based book, interested teachers will be challenged to think through the methods they currently use in their own classes and will be provided new ideas or strategies to try.